Estimation of Radiation Dose from Most Common Pediatrics Radiographic Examinations within Main Central Hospitals in Najaf City, Iraq (Baghdad Science Journal, 2022)
In this study the Entrance Surface Dose (ESD) received by pediatrics patients undergoing chest, abdomen and skull X-ray examinations was estimated. The study was conducted in two hospitals in Najaf city where three radiographic systems were considered. The study participants were classified into four age groups 0-1 , 1-5 , 5-10 and 10-15 years. Calculations were performed using exposure factors, kVp, mAs and focal-skin distance, together with patient data age. The ESD was calculated for the involved patients who underwent an Antero-posterior (AP) chest, abdomen and skull X-ray examination. The resulted data were analyzed and compared with international dose references. For all studied radiographic examinations and all X-ray machines, the ESD increases with age. The lowest recorded radiation dose was from hospital 1 machine 2. In this facility ESD ranged from 19.93 µGy to 67.66 µGy for chest X-ray, from 39.03 µGy to 82.63 µGy for abdomen (AP), and from 35.47 µGy to 94.27 µGy for skull (AP). In contrast the highest dose levels are recorded from hospital 2 machine 1; the minimum ESD for chest X-ray is 247.51 µGy and the maximum is 2393.12 µGy; for abdomen X-ray the lowest ESD is 269.05 µGy and the highest value is 5106.15 µGy; and for skull X-ray minimum values is 430.96 µGy and the maximum value is 3072.77 µGy. In conclusion, for the considered pediatrics examinations, most of ESD values are within the international acceptable level and some are higher >100% .